YELLOWSTONE WOLF DENSITY PREDICTED BY ELK BIOMASS - Mech, L. David; Barber-Meyer, Shannon (NRC Research Press (a division of Canadian Science Publishing), 2015)
The Northern Range (NR) of Yellowstone National Park (YNP) hosts a higher prey biomass density in the form of elk (Cervus elaphus Linnaeus 1758) than any other system of gray wolves (Canis lupus Linnaeus 1758) and prey reported. Therefore it is important to determine whether that wolf-prey system fits a long-standing model relating wolf density to prey biomass. Using data from 2005-2012 after elk population fluctuations dampened 10 years subsequent to wolf reintroduction, we found that NR prey biomass predicted wolf density. This finding and the trajectory of the regression extend the validity of the model to prey densities 19% higher than previous data and suggest that the model would apply to wolf-prey systems of even higher prey biomass. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.